Studies in language testing (Cambridge, U.K., 2000)
The focus on careful reading in the theoretical literature has meant that we have somewhat ignored reading behaviours such as skimming, scanning and search reading in the teaching and testing of reading. These theories do not explain how readers process texts quickly and selectively. The development of the Advanced English Reading Test (AERT) for University students in the People's Republic of China under the auspices of the National College English Test Committee was the vehicle for investigating the nature of and the relationships between skimming, scanning, search reading and careful reading. This volume reports on the methodological procedures that led to the development of this important test and discusses the results of the empirical investigations that were carried out to establish its validity. As such it offers a blueprint of reading assessment for those wishing to research in the area.
Keywords: Education,Education; Assessment,Tests,Setting